2008
DOI: 10.1517/13543776.18.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne hexacarbonyl dicobalt complexes in medicinal chemistry and drug development

Abstract: Background : Organometallic alkyne complexes of the hexacarbonyl dicobalt type (hexacarbonyl[ µ -h 4 -(alkyne)]dicobalt (Co -Co) complexes) are an interesting class of compounds used in modern synthetic chemistry and an increasing number of reports deal also with the use of these complexes in the field of medicinal chemistry. Methods : This review highlights the applications of alkyne hexacarbonyl dicobalt species in biomedical research with a focus on anticancer drug development. Medline, Pubmed, Scifinder an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 54 publications
1
31
0
1
Order By: Relevance
“…Such a dramatic effect by replacing a CO ligand with a cyanide we have observed before in a related octahedral scaffold. [19] Although isoelectronic, coordinated CO is hydrophobic, [20,21] whereas coordinated cyanide tends to form hydrogen bonds with its nitrogen lone pair and will therefore not have any desire to bind into the hydrophobic pocket build by the glycine-rich loop. [22,23] These examples demonstrate the importance of the CO group and, in fact, we have yet to find a highly potent and selective ruthenium complex for GSK-3 that lacks this apparently crucial CO ligand.…”
mentioning
confidence: 99%
“…Such a dramatic effect by replacing a CO ligand with a cyanide we have observed before in a related octahedral scaffold. [19] Although isoelectronic, coordinated CO is hydrophobic, [20,21] whereas coordinated cyanide tends to form hydrogen bonds with its nitrogen lone pair and will therefore not have any desire to bind into the hydrophobic pocket build by the glycine-rich loop. [22,23] These examples demonstrate the importance of the CO group and, in fact, we have yet to find a highly potent and selective ruthenium complex for GSK-3 that lacks this apparently crucial CO ligand.…”
mentioning
confidence: 99%
“…6), is a common mechanism of action for many anti-cancer drugs [42] including cisplatin [43]. As well, the PC-3 cell death caused by three of the most active cobalt compounds (L 1 Co, L 2 Co, and L 3 Co) appears dependent on activation of MAP kinases, and JNK in particular, a mechanism that has also been widely implicated in apoptosis as induced by cisplatin and other anti-cancer drugs [12,44].…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…Ott et al have reported the synthesis and antitumor efficacy of [2-acetoxy-(2-propynyl)benzoate] hexacarbonyldicobalt [11]. Its mode of activity against cancer cells is unknown but it has been suggested that these complexes may interact with DNA or DNA-related cellular biochemical pathways [12]. A number of cobalt(III) complexes have been examined for their antiviral properties, with the most significant development being the approval of Doxovir as a topical microbicide for the treatment of herpes simplex virus type 1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among its many other demonstrated biological effects was a strong induction of caspase-3, which is an important activator in apoptosis. Several other anticancer (hexacarbonyldicobalt)alkyne compounds have also been reported [16]; in all cases, the bioactivities of these compounds have been shown to depend on both the hexacarbonyldicobalt moiety and the organic ligand.…”
Section: Introductionmentioning
confidence: 99%